Embryogenic Calli Induction and Salt Stress Response Revealed by RNA-Seq in Diploid Wild Species Gossypium sturtianum and Gossypium raimondii - Nie, Hushuai; Wang, Yali; Wei, Chengcheng; Grover, Corrinne E.; Su, Ying; Wendel, Jonathan F.; Hua, Jinping (Frontiers in Plant Science, 2021)
Wild cotton species can contribute a valuable gene pool for the genetic improvement, such as genes related to salt tolerance. However, reproductive isolation of different species poses an obstacle to produce hybrids through conventional breeding. Protoplast fusion technology for somatic cell hybridization provides an opportunity for genetic manipulation and targeting of agronomic traits. Transcriptome sequencing analysis of callus under salt stress is conducive to study salt tolerance genes. In this study, calli were induced to provide materials for extracting protoplasts, and also for screening salt-tolerance genes. Calli were successfully induced from leaves of Gossypium sturtianum (C1 genome) and hypocotyls of G. raimondii (D5 genome), and embryogenic callus of G. sturtianum and G. raimondii were induced on differentiation medium with different concentrations of 2, 4-D, KT and IBA, respectively. In addition, embryogenic calli were also induced successfully from G. raimondii through suspension cultivation. Transcriptome sequencing analysis was performed on the calli of G. raimondii and G. sturtianum, which were treated with 200 mM NaCl at 0 h, 6 h, 12 h, 24 h and 48 h, and a total of 12,524 genes were detected with different expression patterns under salt stress. Functional analysis of 3,482 genes, which were differentially expressed in calli of G. raimondii and G. sturtianum, were associated with biological processes of nucleic acid binding, plant hormone (such as ABA) biosynthesis, and signal transduction. We demonstrated that DEGs or TFs which related to ABA metabolism were involved in the response to salt stress, including Xanthoxin dehydrogenase genes (ABA2), Sucrose non-fermenting 1-related protein kinases (SnRK2), NAM, ATAT1/2, and CUC2 transcription factors (NAC), and WRKY class of zinc-finger proteins (WRKY). This research has successfully induced calli from two diploid cotton species, and revealed new genes responding to salt stress in callus tissue, which will lay the foundation for protoplast fusion for further understanding of salt stress responses in cotton.